One-step synthesis and densification uniform BaZr0.1Ce0.7Y0.1Yb0.1O3-δ by step-wise current reactive flash sintering. Issue 23 (1st December 2022) - Gou, Yunjie; Zhao, Yating; Zhang, Jing; Sun, Wang; Qiao, Jinshuo; Sun, Kening; Wang, Zhenhua
Abstract: BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3-δ (BZCYYb) has been widely adopted as the electrolyte for protonic ceramic fuel cells (PCFCs). However, the synthesis and densification process of BZCYYb is too complex, which has greatly hindered the application of PCFCs. In this work, for the first time, we synthesized and densified uniform BZCYYb electrolytes within one step via step-wise current reactive flash sintering (SCRFS). Direct current is applied to the BZCYYb oxide precursor, and the input electric energy is converted into Joule heat, so that the sample can achieve synthesis and densification within 10 min. Compared with reactive flash sintering (RFS), the step-wise current control in SCRFS restricts the heating rate to ensure a uniform microstructure. When the current limit is 1.2 A (160 mA mm −2 ), the relative density is as high as 93.9%, and the sample has good conductivity. Therefore, SCRFS provides a new approach for the manufacture of BZCYYb electrolytes, and has the potential to be applied to achieve one-step uniform synthesis and densification of various ceramics.